Complete sequence and comparative analysis of the chloroplast genome of Gelsemium elegans - Zhenlu Wang; Shulin Liu; Zhuolin Sun; Mingzhi Li; Aiguo Zhou; Shaolin Xie; Jixing Zou; Qiong Xiang; En-Feng Song (Mitochondrial DNA. Part B. Resources, 2019)
In this study, we show the complete chloroplast genome in G. elegans by high-throughput sequencing. The chloroplast genome in G. elegans is 155,018 bp in size, comprising a pair of inverted repeats (IRa and IRb) of 25,728 bp each and an LSC region of 85,619 bp and an SSC region of 17,943 bp. The genome includes 117 single-copy genes (29 tRNA, 8 rRNA genes and 80 protein-coding). Phylogenetic analysis using total chloroplast genome DNA sequence of 15 species belonging to Gentianales showed that Apocynaceae and Loganiaceae form a single cluster with closer relationship to Gentianaceae than with Rubiaceae.